High-strength and high-thermal-conductivity magnesium alloy plate and preparation method thereof
By designing the composition and process of the Mg-Zn-X-Mn alloy in the magnesium alloy, and regulating its structure and properties, the problem of difficulty in improving the strength and thermal conductivity of the magnesium alloy synergistically is solved, and magnesium with high strength and high thermal conductivity is realized. Alloy plates are suitable for aerospace and other fields.
Patent Information
- Application Number
- CN202411476328.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The strength and thermal conductivity of existing magnesium alloys are difficult to improve in concert, resulting in performance bottlenecks in applications in aerospace and other fields.
Using Mg-Zn-X-Mn alloy, through smelting, homogenization heat treatment and rolling deformation process, the alloy composition is designed so that the main second phase is the W phase (such as Mg3Zn3RE2) with favorable thermal conductivity, and the alloy structure is controlled to be a dual-mode structure. And reduce the content of solute atoms in the matrix through dynamic precipitation.
The synergistic improvement of the high strength and high thermal conductivity of magnesium alloy is achieved. The tensile yield strength can reach 340~370MPa, the tensile strength is 360~400MPa, and the room temperature thermal conductivity is 130~140W/(m·K), which meets the requirements Performance requirements in aerospace and other fields.
Smart Images

Figure CN119351842A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of magnesium alloy performance, and in particular to a high-strength and high-thermal-conductivity rolled magnesium alloy and a preparation method thereof. Background Art
[0002] Magnesium alloy is the lightest metal structural material, with high specific stiffness and specific strength, good hot formability, excellent electromagnetic shielding performance and high thermal conductivity. It is the most promising lightweight metal structural material in the fields of aerospace, deep space exploration, military and national defense, transportation, 3C products, etc. In addition, major equipment in the aerospace field contains complex high-power electronic components, and electronic equipment frequently fails due to overheating. In addition to being light and strong, its structural materials must also have high thermal conductivity. Therefore, the production technology of high-strength and high-thermal conductivity magnesium alloy materials and their products plays an important role in achieving the lightweight of the above-mentioned equipment, improving the system operation stability and service life, and has great application value.
[0003] In the field of high-end aerospace equipment, such as satellite radar antenna backplanes and other structural materials, high-strength and high-thermal conductivity magnesium alloy plates are needed. At present, the room temperature thermal conductivity of commercial AZ91 rolled plates is 61W / (m·K), and the tensile strength is 285MPa. The room temperature thermal conductivity of WE43 rolled plates is 51W / (m·K), and the tensile strength is 260MPa. From the analysis of the strengthening and toughening mechanism of magnesium alloys and the key factors of alloy thermal conductivity, it can be seen that the strength and thermal conductivity of magnesium alloys show an inverted relationship. Almost all major strengthening mechanisms such as fine grain strengthening, solid solution strengthening and dislocation strengthening tend to reduce thermal conductivity, which is related to the scattering of electrons by solid solution atoms, dislocations and grain boundaries as lattice defects. Therefore, there is a bottleneck problem that thermal conductivity and mechanical properties are difficult to improve synergistically. The thermal conductivity and mechanical properties of the currently developed magnesium alloy plates are still difficult to meet the application goals of high strength and high thermal conductivity at the same time. Therefore, alloying methods are developed to regulate the element distribution and phase distribution through heat treatment, and rolling deformation is used to regulate the microstructure, mechanical properties and thermal conductivity of the alloy in order to achieve a synergistic improvement of the two. The preparation of high-strength and high-thermal conductivity rolled magnesium alloy plates is of great significance to aerospace, transportation, military industry and national defense. Summary of the invention
[0004] In view of the problems that the existing magnesium alloys have low strength and it is difficult to improve the thermal conductivity and mechanical properties in a coordinated manner, the present invention proposes a high-strength and high-thermal conductivity magnesium alloy plate and a preparation method thereof.
[0005] The high-strength and high-thermal-conductivity magnesium alloy sheet of the present invention is a Mg-Zn-X-Mn alloy, wherein the Zn element content is 1.0% to 7.0%, the Mn element content is 0.2% to 2.0%, the X element content is 1.5% to 7.0%, Mg is the balance, and the X element is one or more of yttrium, gadolinium, neodymium, and erbium;
[0006] The method for preparing the high-strength and high-thermal-conductivity magnesium alloy sheet of the present invention is carried out according to the following steps:
[0007] 1. Weigh the raw materials according to the mass percentage of each element in the Mg-Zn-X-Mn alloy and perform cleaning pretreatment;
[0008] The raw materials are pure Mg ingots, Mg-Zn master alloys, Mg-X master alloys and Mg-Mn master alloys;
[0009] The method for pre-treating the raw materials is: using sandpaper to polish and remove surface impurities and oxide scale;
[0010] 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, cooling it to obtain an alloy ingot, and finally removing the oxide layer on the surface of the alloy ingot and performing a homogenization heat treatment;
[0011] The temperature of the preheating treatment is 290-450°C;
[0012] The protective atmosphere gas is a mixed gas of CO2 and SF6, and the volume ratio of SF6 in the mixed gas is 1.5% to 3.5%;
[0013] The smelting process is as follows: firstly, pure Mg ingot and Mg-Zn master alloy are melted at 690°C to 760°C, then Mg-X master alloy and Mg-Mn master alloy are added, and after being completely melted, the temperature is kept for 30 minutes, and then stirred; after the stirring is completed, the temperature is lowered to 680°C, and the temperature is left to stand for 10 to 20 minutes, and the magnesium alloy melt is water-cooled in a protective atmosphere to form an alloy ingot;
[0014] The stirring time is 3 to 5 minutes;
[0015] The homogenization treatment is performed at a temperature of 450 to 520° C. for a time of 2 to 12 hours;
[0016] 3. The alloy obtained in step 2 is prepared into a billet, the billet is subjected to rolling deformation, and finally air cooling treatment, and the process is completed;
[0017] The thickness of the blank is 10 to 30 mm;
[0018] The method also includes a preheating step of the blank and the roller before the rolling deformation; the preheating temperature of the blank is 290-450°C, the preheating temperature of the roller is 200-350°C, and the preheating time is 10-35 minutes;
[0019] The rolling deformation process is as follows: multiple rolling passes, the deformation amount of the first pass is 10%, the deformation amount of the subsequent passes gradually increases, the increment is 5%, and the cumulative deformation amount is 60-97%; the rolling rate is 0.5-6m / s; annealing is performed between passes, and the annealing temperature is the same as the preheating temperature of the billet;
[0020] The annealing time between the passes is: 15 minutes for a blank with a thickness of more than 5 mm, 10 minutes for a blank with a thickness of 3 to 5 mm, and 5 minutes for a blank with a thickness of less than 3 mm;
[0021] The principles and beneficial effects of the present invention are as follows:
[0022] 1. The present invention selects favorable alloying elements with high strength and high thermal conductivity, and realizes high-strength and high-thermal conductivity rolled magnesium alloy with excellent mechanical properties and thermal conductivity through smelting, homogenization heat treatment and rolling deformation process. The alloy composition is designed to make its main second phase a W phase with favorable thermal conductivity (such as Mg3Zn3RE2), and the alloy structure is regulated by hot rolling deformation to be a dual-mode structure composed of long deformed grains and fine recrystallized grains, and dynamic precipitation is promoted to reduce the solute atom content in the matrix, breaking through the bottleneck problem that strength and thermal conductivity are difficult to improve synergistically. And the technology is mature and can achieve large-scale production, providing technical guidance for the development of high-strength and high-thermal conductivity magnesium alloy sheets.
[0023] 2. The tensile yield strength of the rolled magnesium alloy prepared by the present invention can reach 340-370MPa, the tensile strength is 360-400MPa, the elongation is 5%-10%, the room temperature thermal conductivity is 130-140W / (m·K), and it has excellent mechanical properties and thermal conductivity. The preparation technology of high-strength and high-thermal conductivity rolled magnesium alloy sheets has been broken through. The performance of the obtained sheets can meet the mechanical properties and thermal conductivity requirements of structural parts in the fields of aerospace, deep space exploration, military industry and national defense, transportation, 3C products, etc., and has broad application prospects.
[0024] 3. In the present invention, the solid solubility of the added Zn can reach 6.2wt.%, and the solid solution aging strengthening is obvious. The lattice distortion caused by the same extranuclear electrons as Mg is small, and it can form a unique W-phase intermetallic compound with rare earth atoms, so the negative impact on the thermal conductivity of the magnesium alloy is also small; the added Mn element has a low solid solubility, a valence of +2, and a strong dynamic nano-precipitation effect; the rare earth element X has a unique extranuclear electron structure, a significant solid solution aging effect, and can form a rare earth texture to improve the mechanical properties; the added Zn element forms a W phase (Mg3Zn3RE2) with Mg and X elements, which is conducive to the precipitation of solute atoms, and the Mn element dynamically precipitates, reduces the matrix solute atom content, and improves the thermal conductivity.
[0025] 4. The present invention can regulate the structure and properties of the Mg-Zn-X-Mn alloy through homogenization heat treatment at 450-520°C and hot rolling at 290-450°C, and adopts multiple hot rolling passes to ensure the smooth forming of the alloy plate. The hot rolling partially breaks the W phase and optimizes the phase distribution, promotes the precipitation of nano-precipitates such as MgZn2, Mg4Zn7 and Mg5Gd, promotes the reduction of Zn and Gd solute atoms, and introduces high-density dislocations and grain boundaries. Therefore, the rolled Mg-Zn-X-Mn alloy has excellent mechanical properties and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The metallographic structure diagram of the cast alloy prepared in Example 1;
[0027] Figure 2 The metallographic structure diagram of the rolled alloy prepared in Example 1;
[0028] Figure 3 This is a tensile engineering stress-engineering strain curve of the rolled alloy prepared in Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.
[0030] Specific implementation method 1: In this implementation method, the high-strength and high thermal conductivity magnesium alloy plate is a Mg-Zn-X-Mn alloy, wherein the Zn element content is 1.0% to 7.0%, the Mn element content is 0.2% to 2.0%, the X element content is 1.5% to 7.0%, Mg is the balance, and the X element is one or more of yttrium, gadolinium, neodymium, and erbium.
[0031] This embodiment has the following beneficial effects:
[0032] 1. This embodiment selects favorable alloying elements with high strength and high thermal conductivity, and realizes high-strength and high-thermal conductivity rolled magnesium alloy with excellent mechanical properties and thermal conductivity through smelting, homogenization heat treatment and rolling deformation process. By designing the alloy composition so that its main second phase is the thermally conductive W phase (such as Mg3Zn3RE2), hot rolling deformation is carried out to adjust the alloy structure to a dual-mode structure composed of long deformed grains and fine recrystallized grains, and promotes dynamic precipitation to reduce the solute atom content in the matrix, breaking through the bottleneck problem that strength and thermal conductivity are difficult to improve synergistically. In addition, the technology is mature and can achieve large-scale production, providing technical guidance for the development of high-strength and high-thermal conductivity magnesium alloy sheets.
[0033] 2. The tensile yield strength of the rolled magnesium alloy prepared in this embodiment can reach 340-370MPa, the tensile strength is 360-400MPa, the elongation is 5%-10%, the room temperature thermal conductivity is 130-140W / (m·K), and it has excellent mechanical properties and thermal conductivity. This is a breakthrough in the preparation technology of high-strength and high-thermal conductivity rolled magnesium alloy sheets. The performance of the resulting sheet can meet the mechanical properties and thermal conductivity requirements of structural parts in the fields of aerospace, deep space exploration, military industry and national defense, transportation, 3C products, etc., and has broad application prospects.
[0034] 3. In the present embodiment, the solid solubility of the added Zn can reach 6.2wt.%, and the solid solution aging strengthening is obvious. The lattice distortion caused by the same extranuclear electrons as Mg is small, and it can form a unique W-phase intermetallic compound with rare earth atoms, so the negative impact on the thermal conductivity of the magnesium alloy is also small; the added Mn element has a low solid solubility, a valence of +2, and a strong dynamic nano-precipitation effect; the rare earth element X has a unique extranuclear electron structure, and the solid solution aging effect is obvious, and it can form a rare earth texture to improve the mechanical properties; the added Zn element forms a W phase (Mg3Zn3RE2) with Mg and X elements, which is beneficial to the precipitation of solute atoms, and the Mn element dynamically precipitates, reduces the matrix solute atom content, and improves the thermal conductivity.
[0035] 4. This embodiment can regulate the microstructure and properties of the Mg-Zn-X-Mn alloy through homogenization heat treatment at 450-520°C and hot rolling at 290-450°C, and adopts multiple hot rolling passes to ensure the smooth forming of the alloy sheet. The hot rolling partially breaks the W phase and optimizes the phase distribution, promotes the precipitation of nano-precipitates such as MgZn2, Mg4Zn7 and Mg5Gd, promotes the reduction of Zn and Gd solute atoms, and introduces high-density dislocations and grain boundaries. Therefore, the rolled Mg-Zn-X-Mn alloy has excellent mechanical properties and thermal conductivity.
[0036] Specific implementation method 2: The preparation method of the high-strength and high-thermal-conductivity magnesium alloy sheet in this implementation method is carried out according to the following steps:
[0037] 1. Weigh the raw materials according to the mass percentage of each element in the Mg-Zn-X-Mn alloy and perform cleaning pretreatment;
[0038] 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, cooling it to obtain an alloy ingot, and finally removing the oxide layer on the surface of the alloy ingot and performing a homogenization heat treatment;
[0039] The smelting process is as follows: firstly, pure Mg ingot and Mg-Zn master alloy are melted at 690°C to 760°C, then Mg-X master alloy and Mg-Mn master alloy are added, and after being completely melted, the temperature is kept for 30 minutes, and then stirred; after the stirring is completed, the temperature is lowered to 680°C, and the temperature is left to stand for 10 to 20 minutes, and the magnesium alloy melt is water-cooled in a protective atmosphere to form an alloy ingot;
[0040] The homogenization treatment is performed at a temperature of 450 to 520° C. for a time of 2 to 12 hours;
[0041] 3. The alloy obtained in step 2 is prepared into a billet, the billet is subjected to rolling deformation, and finally air cooling treatment, and the process is completed;
[0042] The method also includes a preheating step of the blank and the roller before the rolling deformation; the preheating temperature of the blank is 290-450°C, the preheating temperature of the roller is 200-350°C, and the preheating time is 10-35 minutes;
[0043] The rolling deformation process is as follows: multiple rolling passes, the deformation amount of the first pass is 10%, the deformation amount of the subsequent passes gradually increases, the increment is 5%, and the cumulative deformation amount is 60-97%; the rolling rate is 0.5-6m / s; annealing is performed between passes, and the annealing temperature is the same as the preheating temperature of the billet;
[0044] The annealing time between the passes is: 15 minutes for blanks with a thickness of more than 5 mm, 10 minutes for blanks with a thickness of 3 to 5 mm, and 5 minutes for blanks with a thickness of less than 3 mm.
[0045] 1. This embodiment selects favorable alloying elements with high strength and high thermal conductivity, and realizes high-strength and high-thermal conductivity rolled magnesium alloy with excellent mechanical properties and thermal conductivity through smelting, homogenization heat treatment and rolling deformation process. By designing the alloy composition so that its main second phase is the thermally conductive W phase (such as Mg3Zn3RE2), hot rolling deformation is carried out to adjust the alloy structure to a dual-mode structure composed of long deformed grains and fine recrystallized grains, and promotes dynamic precipitation to reduce the solute atom content in the matrix, breaking through the bottleneck problem that strength and thermal conductivity are difficult to improve synergistically. In addition, the technology is mature and can achieve large-scale production, providing technical guidance for the development of high-strength and high-thermal conductivity magnesium alloy sheets.
[0046] 2. The tensile yield strength of the rolled magnesium alloy prepared in this embodiment can reach 340-370MPa, the tensile strength is 360-400MPa, the elongation is 5%-10%, the room temperature thermal conductivity is 130-140W / (m·K), and it has excellent mechanical properties and thermal conductivity. This is a breakthrough in the preparation technology of high-strength and high-thermal conductivity rolled magnesium alloy sheets. The performance of the resulting sheet can meet the mechanical properties and thermal conductivity requirements of structural parts in the fields of aerospace, deep space exploration, military industry and national defense, transportation, 3C products, etc., and has broad application prospects.
[0047] 3. In the present embodiment, the solid solubility of the added Zn can reach 6.2wt.%, and the solid solution aging strengthening is obvious. The lattice distortion caused by the same extranuclear electrons as Mg is small, and it can form a unique W-phase intermetallic compound with rare earth atoms, so the negative impact on the thermal conductivity of the magnesium alloy is also small; the added Mn element has a low solid solubility, a valence of +2, and a strong dynamic nano-precipitation effect; the rare earth element X has a unique extranuclear electron structure, and the solid solution aging effect is obvious, and it can form a rare earth texture to improve the mechanical properties; the added Zn element forms a W phase (Mg3Zn3RE2) with Mg and X elements, which is beneficial to the precipitation of solute atoms, and the Mn element dynamically precipitates, reduces the matrix solute atom content, and improves the thermal conductivity.
[0048] 4. This embodiment can regulate the microstructure and properties of the Mg-Zn-X-Mn alloy through homogenization heat treatment at 450-520°C and hot rolling at 290-450°C, and adopts multiple hot rolling passes to ensure the smooth forming of the alloy sheet. The hot rolling partially breaks the W phase and optimizes the phase distribution, promotes the precipitation of nano-precipitates such as MgZn2, Mg4Zn7 and Mg5Gd, promotes the reduction of Zn and Gd solute atoms, and introduces high-density dislocations and grain boundaries. Therefore, the rolled Mg-Zn-X-Mn alloy has excellent mechanical properties and thermal conductivity.
[0049] Specific implementation method three: The difference between this implementation method and specific implementation method two is that the raw materials in step one are pure Mg ingots, Mg-Zn master alloys, Mg-X master alloys and Mg-Mn master alloys.
[0050] Specific implementation method 4: This implementation method is different from specific implementation method 2 in that: the method for pre-treating the raw materials in step 1 is: using sandpaper to polish and remove surface impurities and oxide scale.
[0051] Specific implementation method five: This implementation method is different from specific implementation method two in that the temperature of the preheating treatment in step two is 290-450°C.
[0052] Specific implementation method six: This implementation method is different from specific implementation method two in that the protective atmosphere gas in step two is a mixed gas of CO2 and SF6, and the volume ratio of SF6 in the mixed gas is 1.5% to 3.5%.
[0053] Specific implementation method seven: This implementation method is different from specific implementation method two in that: the stirring time in step two is 3 to 5 minutes.
[0054] Specific implementation eight: This implementation differs from specific implementation two in that: the thickness of the blank in step three is 10 to 30 mm.
[0055] Specific embodiment nine: This embodiment differs from specific embodiment two in that: in the Mg-Zn-X-Mn alloy described in step one, the Zn element content is 1.0% to 7.0%, the Mn element content is 0.2% to 2.0%, the X element content is 1.5% to 7.0%, Mg is the remainder, and the X element is one or more of yttrium, gadolinium, neodymium, and erbium.
[0056] Specific embodiment ten: The present embodiment is different from specific embodiment two in that: the smelting process described in step two is: firstly melt the pure Mg ingot and Mg-Zn master alloy at 760°C, then add the Mg-X master alloy and the Mg-Mn master alloy, keep warm for 30 minutes after they are completely melted, and then stir; after stirring, cool to 680°C, let stand for 15 minutes, and water-cool the magnesium alloy melt under a protective atmosphere to form an alloy ingot.
[0057] Example 1
[0058] The method for preparing the high-strength and high-thermal-conductivity magnesium alloy sheet of this embodiment is carried out according to the following steps:
[0059] 1. Weigh the raw materials according to the mass percentage of each element in the Mg-Zn-Gd-Mn alloy and perform cleaning pretreatment;
[0060] In the Mg-Zn-Gd-Mn alloy, the Zn element content is 4.82%, the Mn element content is 0.43%, the Gd element content is 5.56%, and the balance is Mg;
[0061] The raw materials are pure Mg ingots, Mg-30wt.% Zn master alloy, Mg-30wt.% Gd master alloy and Mg-5wt.% Mn master alloy;
[0062] The method for pre-treating the raw materials is: using sandpaper to polish and remove surface impurities and oxide scale;
[0063] 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, cooling it to obtain an alloy ingot, and finally removing the oxide layer on the surface of the alloy ingot and performing a homogenization heat treatment;
[0064] The temperature of the preheating treatment is 390°C;
[0065] The protective atmosphere gas is a mixed gas of CO2 and SF6, and the volume ratio of SF6 in the mixed gas is 2.6%;
[0066] The smelting process is as follows: firstly, pure Mg ingot and Mg-Zn master alloy are melted at 760°C, then Mg-Gd master alloy and Mg-Mn master alloy are added, and after being completely melted, the temperature is kept for 30 minutes, and then stirred; after the stirring is completed, the temperature is lowered to 680°C, and the temperature is left to stand for 15 minutes, and the magnesium alloy melt is water-cooled in a protective atmosphere to form an alloy ingot;
[0067] The stirring time is 5 min;
[0068] The homogenization treatment was performed at a temperature of 500°C for 7 hours.
[0069] 3. The alloy obtained in step 2 is prepared into a billet, the billet is subjected to rolling deformation, and finally air cooling treatment, and the process is completed;
[0070] The thickness of the blank is 10 mm;
[0071] The method also includes a preheating step of the blank and the roller before the rolling deformation; the preheating temperature of the blank is 390°C, the preheating temperature of the roller is 260°C, and the preheating time is 30 minutes;
[0072] The rolling deformation process is as follows: multiple rolling passes, the deformation amount of the first pass is 10%, the deformation amount of the subsequent passes gradually increases, the increment is 5%, and the cumulative deformation amount is 70%; the rolling rate is 2m / s; annealing is performed between passes, and the annealing temperature is the same as the preheating temperature of the billet;
[0073] The annealing time between the passes is: 15 minutes for a blank with a thickness of more than 5 mm, 10 minutes for a blank with a thickness of 3 to 5 mm, and 5 minutes for a blank with a thickness of less than 3 mm;
[0074] The rolled Mg-4.82Zn-5.56Gd-0.43Mn alloy prepared in this embodiment has a yield strength of 341.9 MPa, a tensile strength of 384.8 MPa, an elongation of 6.5%, and a thermal conductivity of 135.6 W / (m·K). The mechanical properties and thermal conductivity are synergistically improved, far exceeding commercial magnesium alloys such as AZ series and WE43.
[0075] Figure 1The metallographic structure diagram of the cast alloy prepared in Example 1; Figure 1 It can be seen that the microstructure of the cast Mg-4.82Zn-5.56Gd-0.43Mn alloy is mainly composed of α-Mg matrix and semi-continuous network eutectic second phase W-Mg3Zn3Gd2, and the W phase has a lamellar structure. Figure 2 The metallographic structure diagram of the rolled alloy prepared in Example 1; Figure 2 It can be seen that after rolling, the semi-continuous network second phase in the alloy is broken into fine particles with a strip-like distribution, and the alloy presents a bimodal grain structure: composed of coarse strip-shaped deformation grains and fine recrystallized grains, with a recrystallized grain size of about 1μm. There are fine strip-shaped twins along the shear direction inside the coarse deformation grains, which significantly improves the mechanical properties of the alloy. Figure 3 The tensile engineering stress-engineering strain curve of the rolled alloy prepared in Example 1. The content of Zn and Gd elements in the alloy is equivalent, forming W phase, and hot rolling promotes dynamic precipitation behavior, fully reduces the solute atom content in the Mg matrix, and improves the thermal conductivity of the alloy. The addition of Mn element fully promotes dynamic precipitation, and in summary, the synergistic improvement of the mechanical properties and thermal conductivity of the magnesium alloy is achieved.
[0076] Embodiment 2:
[0077] The difference between this embodiment and embodiment 1 is that: the preheating temperature of the billet before rolling deformation in step 3 is 420°C and the time is 30 minutes; the cumulative deformation amount of rolling deformation is 90%, and the rolling rate is 2m / min. The rest is the same as embodiment 1.
[0078] The rolled Mg-4.82Zn-5.56Gd-0.43Mn alloy prepared in this embodiment has a yield strength of 330.2 MPa, a tensile strength of 371.6 MPa, an elongation of 8.6%, and a thermal conductivity of 137.3 W / (m·K).
[0079] Embodiment 3:
[0080] The difference between this embodiment and embodiment 2 is that in the Mg-Zn-Gd-Mn alloy, the content of Zn is 5.16wt.%, the content of Gd is 5.27wt.%, the content of Mn is 0.38wt.%, and the balance is Mg. The rest is the same as embodiment 2.
[0081] The extruded Mg-5.16Zn-5.27Gd-0.38Mn alloy prepared in this embodiment has a yield strength of 332.2 MPa, a tensile strength of 373.6 MPa, an elongation of 8.5%, and a thermal conductivity of 136.8 W / (m·K).
[0082] Embodiment 4:
[0083] The difference between this embodiment and embodiment 3 is that in the Mg-Zn-Gd-Mn alloy, the content of Zn is 4.69wt.%, the content of Gd is 4.93wt.%, the content of Mn is 0.45wt.%, and the balance is Mg. The rest is the same as embodiment 3.
[0084] The rolled Mg-4.69Zn-4.93Gd-0.45Mn alloy prepared in the embodiment has a yield strength of 348.6 MPa, a tensile strength of 392.8 MPa, an elongation of 5.4%, and a thermal conductivity of 132.8 W / (m·K).
[0085] Embodiment 5:
[0086] The difference between this embodiment and embodiment 4 is that in the Mg-Zn-Gd-Mn alloy, the content of Zn is 5.62wt.%, the content of Gd is 5.83wt.%, the content of Mn is 0.50wt.%, and the balance is Mg. The rest is the same as embodiment 4.
[0087] The rolled Mg-5.62Zn-5.83Gd-0.50Mn alloy prepared in the embodiment has a yield strength of 350.4 MPa, a tensile strength of 398.9 MPa, an elongation of 4.2%, and a thermal conductivity of 130.6 W / (m·K).
Claims
1. A high-strength and high-thermal-conductivity magnesium alloy sheet, characterized in that: The high-strength and high-thermal-conductivity magnesium alloy plate is a Mg-Zn-X-Mn alloy, wherein the Zn element content is 1.0% to 7.0%, the Mn element content is 0.2% to 2.0%, the X element content is 1.5% to 7.0%, Mg is the balance, and the X element is one or more of yttrium, gadolinium, neodymium, and erbium.
2. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The preparation method of the high-strength and high-thermal-conductivity magnesium alloy sheet is carried out according to the following steps:
1. Weigh the raw materials according to the mass percentage of each element in the Mg-Zn-X-Mn alloy and perform cleaning pretreatment; 2. Preheating the raw material after the treatment in step 1, then smelting it in a protective atmosphere, cooling it to obtain an alloy ingot, and finally removing the oxide layer on the surface of the alloy ingot and performing a homogenization heat treatment; The smelting process is as follows: firstly, pure Mg ingot and Mg-Zn master alloy are melted at 690°C to 760°C, then Mg-X master alloy and Mg-Mn master alloy are added, and after being completely melted, the temperature is kept for 30 minutes, and then stirred; after the stirring is completed, the temperature is lowered to 680°C, and the temperature is left to stand for 10 to 20 minutes, and the magnesium alloy melt is water-cooled in a protective atmosphere to form an alloy ingot; The homogenization treatment is performed at a temperature of 450 to 520° C. for a time of 2 to 12 hours; 3. The alloy obtained in step 2 is prepared into a billet, the billet is subjected to rolling deformation, and finally air cooling treatment, and the process is completed; The method also includes a preheating step of the blank and the roller before the rolling deformation; the preheating temperature of the blank is 290-450°C, the preheating temperature of the roller is 200-350°C, and the preheating time is 10-35 minutes; The rolling deformation process is as follows: multiple rolling passes, the deformation amount of the first pass is 10%, the deformation amount of the subsequent passes gradually increases, the increment is 5%, and the cumulative deformation amount is 60-97%; the rolling rate is 0.5-6m / s; annealing is performed between passes, and the annealing temperature is the same as the preheating temperature of the billet; The annealing time between the passes is: 15 minutes for a blank with a thickness of more than 5 mm, 10 minutes for a blank with a thickness of 3 to 5 mm, and 5 minutes for a blank with a thickness of less than 3 mm.
3. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The raw materials in step 1 are pure Mg ingots, Mg-Zn master alloys, Mg-X master alloys and Mg-Mn master alloys.
4. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The method for cleaning and pre-treating the raw materials in step 1 is: using sandpaper to polish and remove surface impurities and oxide scale.
5. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The temperature of the preheating treatment in step 2 is 290-450°C.
6. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The protective atmosphere gas in step 2 is a mixed gas of CO2 and SF6, and the volume ratio of SF6 in the mixed gas is 1.5% to 3.5%.
7. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The stirring time in step 2 is 3 to 5 minutes.
8. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The thickness of the blank in step 3 is 10 to 30 mm.
9. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: In the Mg-Zn-X-Mn alloy of step 1, the Zn element content is 1.0% to 7.0%, the Mn element content is 0.2% to 2.0%, the X element content is 1.5% to 7.0%, Mg is the balance, and the X element is one or more of yttrium, gadolinium, neodymium, and erbium.
10. The method for preparing a high-strength and high-thermal-conductivity magnesium alloy sheet according to claim 1, characterized in that: The smelting process of step 2 is as follows: firstly, pure Mg ingot and Mg-Zn master alloy are melted at 760°C, and then Mg-X master alloy and Mg-Mn master alloy are added, and after complete melting, they are kept warm for 30 minutes, and then stirred; after stirring, the temperature is lowered to 680°C, and allowed to stand for 15 minutes, and the magnesium alloy melt is water-cooled in a protective atmosphere to form an alloy ingot.
Citation Information
Patent Citations
High-strength high-plasticity medical magnesium alloy, and preparation method and applications thereof
CN104862566A
Magnesium-zinc-manganese-gadolinium magnesium alloy with high strength and high plasticity as well as preparation method thereof
CN108103375A
Magnesium alloy anastomosis nail with fine control performance and preparation method thereof
CN111434791A
Apparatus and method thereof for water pipe using low nitrogen
KR102101122B1
Cited By
Magnesium alloy and preparation method therefor, structural member, and electronic device
WO2026194635A1